PENERAPAN METHODE ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK PEMILIHAN JURUSAN PADA SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU (PPDB) - Siti Ramah; Rizkayeni Marta; Elfi Tasrif (Pojok Publisher, 2025)
The admission of new students at SMK N 11 Merangin has two stages of selection, namely the selection of new student admissions and the determination of majors. The process of accepting new students is carried out offline. Based on data from BK teachers and observations during the educational field practice in July-December 2022, it was found that many students still felt unsuitable for the majors they had chosen. In this study, the method used in system development is the System Development Life Cycle (SDLC) waterfall model which includes requirements analysis, system and software design, implementation, testing, and maintenance. This application has been compiled using the PHP programming language and the Codeigniter Framework, and is supported by the MySQL database. In the development process, several additional applications that play a role are XAMPP, the Google Chrome browser, Visual Studio Code, and the CSS Bootstrap Framework which is used to design the system display. Based on the purpose of designing the application of the Analytical Hierarchy Process (AHP) method for selecting majors in the web-based new student admissions information system (PPDB) at SMK N 11 Merangin which has been carried out, it can be concluded that the results of this final assignment are to produce a web-based application for selecting majors in the new student admissions information system (PPDB) at SMK N 11 Merangin in managing new student admissions and major selection.